If the ${m^{th}}$ term of an A.P be $\dfrac{1}{n}$ and ${n^{th}}$ term be $\dfrac{1}{m}$ , then show that its ${(mn)^{th}}$ term is 1.
Answer
Verified
510k+ views
Hint: Here, we will use the Arithmetic Progression Concept and the ${n^{th}}$term formulae i.e..,${T_n} = a + (n - 1)d$.
Complete step-by-step answer:
Given,
The ${m^{th}}$term of an A.P is $\dfrac{1}{n}$ and ${n^{th}}$term is $\dfrac{1}{m}$
Now, let us consider ‘a’ be the first term and‘d’ is the common difference of an A.P.As, we know that the ${n^{th}}$term of an A.P will be ${T_n} = a + (n - 1)d$.
Therefore, the ${m^{th}}$ term can be written as
$
\Rightarrow {m^{th}}term = \dfrac{1}{n} \\
\Rightarrow \dfrac{1}{n} = a + (m - 1)d \to (1) \\
$
Similarly, the ${n^{th}}$term is given as $\dfrac{1}{m}$, it can be written as
$
\Rightarrow {n^{th}}term = \dfrac{1}{m} \\
\Rightarrow \dfrac{1}{m} = a + (n - 1)d \to (2) \\
$
Let us subtract equation (2) from equation (1), we get
$
\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = a + (m - 1)d - a - (n - 1)d \\
\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = md - d - nd + d \\
\Rightarrow \dfrac{{m - n}}{{mn}} = (m - n)d \\
\Rightarrow \dfrac{1}{{mn}} = d \\
$
Hence, we obtained the value of d i.e.., $\dfrac{1}{{mn}}$.Now let us substitute the obtained value of d in equation (1), we get
$
(1) \Rightarrow \dfrac{1}{n} = a + (m - 1)d \\
\Rightarrow \dfrac{1}{n} = a + \dfrac{{(m - 1)}}{{mn}} \\
\Rightarrow \dfrac{1}{n} = a + \dfrac{1}{n} - \dfrac{1}{{mn}} \\
\Rightarrow \dfrac{1}{n} - \dfrac{1}{n} + \dfrac{1}{{mn}} = a \\
\Rightarrow \dfrac{1}{{mn}} = a \\
$
Hence, here also we got the value of ‘a’ as $\dfrac{1}{{mn}}$.Therefore, we can say
$a = d = \dfrac{1}{{mn}}$
Now, we need to find the ${(mn)^{th}}$term which is equal to ‘$a + (mn - 1)d$’.So substituting the obtained values of ‘a’ and d’ we get
$
\Rightarrow {(mn)^{th}}term = a + (mn - 1)d = \dfrac{1}{{mn}} + (mn - 1)(\dfrac{1}{{mn}}) = \dfrac{1}{{mn}} + 1 - \dfrac{1}{{mn}} = 1 \\
\Rightarrow {(mn)^{th}}term = 1 \\
$
Hence, we proved that the value of ${(mn)^{th}}$term is$1$.
Note: In an AP, d is the common difference of the consecutive terms i.e..,${t_3} - {t_2} = {t_2} - {t_1} = {t_n} - {t_{n - 1}} = d$.
Complete step-by-step answer:
Given,
The ${m^{th}}$term of an A.P is $\dfrac{1}{n}$ and ${n^{th}}$term is $\dfrac{1}{m}$
Now, let us consider ‘a’ be the first term and‘d’ is the common difference of an A.P.As, we know that the ${n^{th}}$term of an A.P will be ${T_n} = a + (n - 1)d$.
Therefore, the ${m^{th}}$ term can be written as
$
\Rightarrow {m^{th}}term = \dfrac{1}{n} \\
\Rightarrow \dfrac{1}{n} = a + (m - 1)d \to (1) \\
$
Similarly, the ${n^{th}}$term is given as $\dfrac{1}{m}$, it can be written as
$
\Rightarrow {n^{th}}term = \dfrac{1}{m} \\
\Rightarrow \dfrac{1}{m} = a + (n - 1)d \to (2) \\
$
Let us subtract equation (2) from equation (1), we get
$
\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = a + (m - 1)d - a - (n - 1)d \\
\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = md - d - nd + d \\
\Rightarrow \dfrac{{m - n}}{{mn}} = (m - n)d \\
\Rightarrow \dfrac{1}{{mn}} = d \\
$
Hence, we obtained the value of d i.e.., $\dfrac{1}{{mn}}$.Now let us substitute the obtained value of d in equation (1), we get
$
(1) \Rightarrow \dfrac{1}{n} = a + (m - 1)d \\
\Rightarrow \dfrac{1}{n} = a + \dfrac{{(m - 1)}}{{mn}} \\
\Rightarrow \dfrac{1}{n} = a + \dfrac{1}{n} - \dfrac{1}{{mn}} \\
\Rightarrow \dfrac{1}{n} - \dfrac{1}{n} + \dfrac{1}{{mn}} = a \\
\Rightarrow \dfrac{1}{{mn}} = a \\
$
Hence, here also we got the value of ‘a’ as $\dfrac{1}{{mn}}$.Therefore, we can say
$a = d = \dfrac{1}{{mn}}$
Now, we need to find the ${(mn)^{th}}$term which is equal to ‘$a + (mn - 1)d$’.So substituting the obtained values of ‘a’ and d’ we get
$
\Rightarrow {(mn)^{th}}term = a + (mn - 1)d = \dfrac{1}{{mn}} + (mn - 1)(\dfrac{1}{{mn}}) = \dfrac{1}{{mn}} + 1 - \dfrac{1}{{mn}} = 1 \\
\Rightarrow {(mn)^{th}}term = 1 \\
$
Hence, we proved that the value of ${(mn)^{th}}$term is$1$.
Note: In an AP, d is the common difference of the consecutive terms i.e..,${t_3} - {t_2} = {t_2} - {t_1} = {t_n} - {t_{n - 1}} = d$.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE